Development of Myanmar web search engine. - Thet, Ye Thura. (2011)
The objective of this study is to develop a web search engine for the Myanmar language. Despite the increase in volume of information available in the Myanmar language on the web, Information Retrieval (IR) for the Myanmar language is still inefficient due to the lack of support for the language by the major search engines.